Mosques in the Digital Era: Contesting Sacred Space, Culture, and the Identity of Generation Z Muslims - Siti Fadilla; Deddy Desmal; Muhammad Ritzky Saibi; Muhammad Deni Putra (Communication and Islamic Broadcasting Study Program, Faculty of Da'wah and Communication, Universitas Islam Negeri Sunan Kalijaga Yogyakarta, Yogyakarta, Indonesia, 2026)
The digital era has transformed mosques from purely sacred spaces into hybrid spaces that integrate both physical and digital dimensions. This study aims to analyze the dynamics of contestation over values, culture, and the identities of Generation Z Muslims during this transformation. Using a critical qualitative literature review, the study explores how negotiations over the meaning of sacredness emerge as worship practices, preaching, and community life in mosques become infused with digital technologies. The findings reveal that digitalization does not necessarily erode sacredness; rather, it becomes a medium for its redefinition, shaped by tensions between traditional authority, local cultural values, and the logic of digital efficiency. Generation Z emerges as a key actor shaping a hybrid Islamic identity by blending ritual piety with digital participation, such as through social media da’wah content and sharia-based financial applications. However, this transformation faces concrete challenges, including gaps in digital infrastructure and literacy among mosque administrators and congregants. The significance of this study lies in its contribution to enriching the discourse in the sociology of religion by positioning technology not merely as a tool, but as part of broader processes of cultural adaptation and identity formation. The study underscores the need for a holistic mosque management approach that balances technological integration with the preservation of the community’s spiritual and cultural values.